2020
DOI: 10.3390/ijms21072343
|View full text |Cite
|
Sign up to set email alerts
|

Different Expression Pattern of TIM-3 and Galectin-9 Molecules by Peripheral and Peritoneal Lymphocytes in Women with and without Endometriosis

Abstract: Endometriosis is a gynecological condition that is associated with chronic pelvic inflammation, pain, and infertility. Although substantial evidence supports that immunological alterations contribute to its pathogenesis and we previously posed a pivotal role of Galectin-9 (Gal-9) in this disorder, the involvement of the TIM-3/Gal-9 pathway in the development of endometriosis-associated immunological abnormalities is not yet known. In the present study, multicolor flow cytometry was used to compare the immunoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…When Tim-3 on NK cells bind to its ligands, its function of secreting cytokines and killing target cells is diminished (20)(21)(22). It has been assumed that the Tim-3-Galectin-9 pathway plays an important role in regulating tumor cells escaping from immune surveillance (23,24). In our study, of all the Tim-3 ligands, only CEACAM1 was expressed on NK-92 cells (about 70%).…”
Section: Nk Cells Are An Important Part Of Innate Immunity and Can Di...mentioning
confidence: 56%
“…When Tim-3 on NK cells bind to its ligands, its function of secreting cytokines and killing target cells is diminished (20)(21)(22). It has been assumed that the Tim-3-Galectin-9 pathway plays an important role in regulating tumor cells escaping from immune surveillance (23,24). In our study, of all the Tim-3 ligands, only CEACAM1 was expressed on NK-92 cells (about 70%).…”
Section: Nk Cells Are An Important Part Of Innate Immunity and Can Di...mentioning
confidence: 56%
“…The immunoregulatory function of Gal-9, its substantial increase during pathologic conditions, and its association with disease severity have been shown previously ( 31 , 32 ). Meggyes et al have also shown an altered pathway for expression of Gal-9 on peripheral blood and fluid lymphocytes of women with endometriosis, compared to those without the disorder, which confirms the role of Gal-9 in the impaired immunologic mechanism of endometriosis ( 33 ). According to the fact that endometriosis is an inflammatory disease that stimulates immune response and inflammation in the body ( 34 ) with numerous immunologic and inflammatory changes ( 35 ), the response to immunologic conditions is mainly impaired in women with endometriosis.…”
Section: Discussionmentioning
confidence: 76%
“…They established the elevated expression of Gal-9 on CD4 + T cells and Tregs in the PB of EMS patients in comparison to healthy subjects. Additionally, the authors demonstrated a higher expression of Gal-9 on the peritoneal CD8 + T cells and NK cells compared with the PB [ 26 ]. Moreover, peritoneal T cell subsets showed an increased TIM-3 expression than in the PB.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, peritoneal T cell subsets showed an increased TIM-3 expression than in the PB. The authors also revealed elevated TIM-3 expression on peritoneal NKT-like cells in the EMS group [ 26 ]. Confronting the literature data with our findings, we suggest that the accumulation of Gal-9 expressing mDCs and pDCs in the peritoneal cavity could represent the hallmark of the immune regulation in women with endometriosis.…”
Section: Discussionmentioning
confidence: 99%